(untitled) (Bangladesh Journal of Botany, 2019)
An attempt was made to study the effect of pinching, plant densities and foliar nutrient sprays on seed yield and quality parameters in China aster cv. Powder puff. The experiment comprised of two levels of pinching (P0 = No pinching, P1 = Pinching), three planting densities (D1 = 30 plants m-2, D2 = 36 plants m-2 and D3 = 42 plants m-2) and three levels of commercial nutrient sprays (S1= 3 sprays, S2= 4 sprays and S3 = 5 sprays), constituting a total of 18 treatment combinations replicated thrice in randomized complete block design (RCBD). Pinching at visible bud stage, significantly increased 1000 seed weight (2.18 g) and seed yield (490.85 kg/ha), Increasing the planting density resulted in increased seed yield (485.55 kg/ha) and 1000 seed weight (2.05 g). On the other hand, 4 and 5 nutrient sprays significantly improved seed yield (463.12 kg/ha-) and 1000 seed weight (1.95 g). The results from the study suggest that increased branching with apical bud removal, wider planting space and 4 to 5 foliar applications of multi-nutrient sprays, significantly improves seed yield and quality attributes of transplanted China aster. While suggesting the best combination of pinching, spacing and nutrient sprays, the economics of flower production was duly considered.